2009
DOI: 10.1111/j.1461-0248.2009.01372.x
|View full text |Cite
|
Sign up to set email alerts
|

A global synthesis of plant extinction rates in urban areas

Abstract: Plant extinctions from urban areas are a growing threat to biodiversity worldwide. To minimize this threat, it is critical to understand what factors are influencing plant extinction rates. We compiled plant extinction rate data for 22 cities around the world. Two-thirds of the variation in plant extinction rates was explained by a combination of the city's historical development and the current proportion of native vegetation, with the former explaining the greatest variability. As a single variable, the amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
215
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 280 publications
(222 citation statements)
references
References 38 publications
4
215
0
3
Order By: Relevance
“…Not surprisingly, greater proportions of intact vegetation in cities, as found in older cities, preserve plant species. These results highlight the importance of including remnant vegetation and restoring natural areas in the design of cities [49].…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Not surprisingly, greater proportions of intact vegetation in cities, as found in older cities, preserve plant species. These results highlight the importance of including remnant vegetation and restoring natural areas in the design of cities [49].…”
Section: Resultsmentioning
confidence: 91%
“…A median of 3.3 species km 22 was found in these cities for native plants and 4.7 species km 22 for all plants (figure 2). The density of native plant species (robust ANOVA, F 1,4 ¼ 14.4, p , 0.001) and all plant species differed among realms (robust ANOVA, F 1,4 ¼ 17.3, p , 0.001), with cities in Indo-Malaya and Australasia having the lowest densities, probably owing to urban development histories [49].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative to non-urban areas, urban areas have dramatically different environmental conditions, such as warmer air temperatures [2] and altered ecological communities [3]. Although urbanization can have large ecological effects on plant and animal communities [4,5], the evolutionary consequences of urbanization are still poorly understood [6][7][8]. In particular, very little is known about whether species exhibit clinal evolution along urbanization gradients and about the ecological mechanisms that cause evolution in urban ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Recent empirical research has shown that, at the scale of individual habitat patches, a delayed response of species to habitat loss and fragmentation is indeed often detectable, particularly among habitat specialists (9)(10)(11). The likelihood and magnitude of extinction debt is still contentious, however (12,13), and seems to vary with the nature of environmental degradation and with the life history traits of the species concerned (14)(15)(16)(17)(18). In long-lived or less-mobile taxa (e.g., vascular plants, bryophytes, reptiles), a delayed response of populations to the deterioration and fragmentation of their habitats is especially likely and might extend over at least several decades.…”
mentioning
confidence: 99%